Lateral epicondyle osteotomy results in improved radiologic and functional outcomes in severe lateral tibial plateau fractures: a retrospective cohort study - Hendrik Fahlbusch; P. Behrendt; A. Becker; C. Arras; H. Gablac; J. Frings; M. Hoffmann; M. Krause; K. H. Frosch (Journal of Orthopaedic Surgery and Research)
Abstract Background This study evaluated the clinical and radiological outcomes of lateral tibial plateau fractures involving the central and postero-lateral regions, comparing an extended lateral approach with lateral epicondyle osteotomy (ECO) to a conventional approach without an extention (No-ECO). Methods A retrospective cohort study was conducted at two centers, examining complex lateral tibial plateau fractures treated with either an extended lateral approach with ECO or without it. Only AO/OTA type B3/C3 fractures involving the antero-latero-central (ALC) and postero-latero-central (PLC) segments were included. Fracture reduction quality was assessed via post-operative CT scans, and clinical outcomes and complications were evaluated over a minimum of 24-month follow-up. Results A total of 110 patients (mean age: 51.3 ± 11.1 years) were included, with an average follow-up of 52.7 ± 16.9 months. The ECO group (n = 56) consisted of more severe injuries, indicated by higher external fixator use (48.2% vs. 22.2%, p = 0.0044) and additional affected segments. Postoperative CT scans revealed that the ECO group had significantly less fracture step-off (0.8 mm vs. 3.0 mm, p = 0.0002) and angulation at the ALC/PLC (8.1° vs. 20.1°, p = 0.0002) segment and PLC/PLL (postero-latero-lateral) (2.2° vs. 7.5°, p = 0.02) segments. Clinically, the ECO group achieved superior IKDC scores (71.7 vs. 63.7, p = 0.0097). A negative correlation was found between postoperative ALC/PLC depression and IKDC scores (r=-0.36, p = 0.0002). Conclusion Patients treated with ECO had a significantly better clinical and radiologic postoperative outcomes, with the quality of fracture reduction positively correlating with the clinical IKDC score. This was achieved despite more severe injuries, as indicated by higher external fixator use and number of affected segments. Level of evidence III Retrospective Cohort Study. Trial registration The study was retrospectively registered and conducted according to the guidelines of the Declaration of Helsinki and approved by the local Ethics Committee (PV7319).